"Deal of the Century": Dimensions of security threats on Jordan - Abu Hazeem, Tareq (Dirasat: Human and Social Sciences, 2022)
This research attempts to trace how the threats of the Deal of the Century affect the Jordanian State according to the dimensions of the security threats. To achieve the objectives of the study, four main hypotheses were tested in practical terms. The first was concerned with future temporal influences, the second one is the intensity of the effects, the third one is the number of effects, and the fourth one is the backlash results. The sample is chosen purposefully and consists of 336 (politicians and media professionals). The data is collected by using a questionnaire which is marked with high reliability and validity. The research was designed according to the descriptive and analytical approach. The results of the research indicate that the overall degree of the average threat of the Deal of the Century on the Jordanian State according to the security threats was high. The research results find strong evidence on the temporal effects of the Deal of the Century in terms of its severity, and the amount of its impact on Jordan. Finally, the research results find that there is a weakness in dealing with the backlash results of the deal of the century, and the research concluded with a set of recommendations.